Market uncertainty and sentiment around USDA announcements - An N. Q. Cao; Michel A. Robe (Journal of Futures Markets, 2021)
We investigate forward-looking commodity price volatility expectations (proxied by option-implied volatilities or IVols) around scheduled US~Department of Agriculture (USDA) reports. We show that corn and soybean IVols are significantly lower for several trading days after a report. The IVol response to a release depends on agricultural market experts' disagreement and sentiment before the USDA report, and on the extent to which the USDA information surprises the market. Whereas commodity IVols are generally positively related to financial-market sentiment and macroeconomic uncertainty (jointly captured by the volatility index [VIX]), this comovement breaks down on report days—with the VIX and commodity IVols moving in opposite directions.
Keywords: 330; commodities; dispersion; forward-looking volatility; market sentiment; scheduled news; surprise